A Dual Watermark-Fingerprint System - Kirovski, D.; Malvar, H. S.; Yacobi, Y.; Kirovski, Darko; Malvar, Henrique S.; Yacobi, Yacov (IEEE Multimedia Magazine, 2004)
A dual-purpose watermarking and fingerprinting system for multimedia screening uses the same secret key to mark all content copies, but different detection keys within each media player. Under optimal attacks, the system’s collusion resistance is superlinear in object size.